2020
DOI: 10.3390/magnetochemistry6010006
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticles

Abstract: Magnetic nanoparticles are a class of nanoparticle that can be manipulated using magnetic fields [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In recent years, developments of magnetic nanoparticles have been receiving significant attention due to a wide range of potential applications and high absorption in the superparamagnetic characteristics, high surface-to-volume ratio, etc [1] . Spinel ferrites are the most attractive ferrite because of the presence of magnetic and electrical properties such as high saturation magnetization (Ms) as well as high dielectric properties and initial permeability, low eddy current loss [2] , [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, developments of magnetic nanoparticles have been receiving significant attention due to a wide range of potential applications and high absorption in the superparamagnetic characteristics, high surface-to-volume ratio, etc [1] . Spinel ferrites are the most attractive ferrite because of the presence of magnetic and electrical properties such as high saturation magnetization (Ms) as well as high dielectric properties and initial permeability, low eddy current loss [2] , [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%
“…The most widely applied examples of magnetic materials are magnetite (Fe 3 O 4 ) and maghemite (γ-Fe 2 O 3 ), which are now used in medicine for diagnostics and the treatment of oncological diseases, drug delivery, etc. [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Besides AuNPs, magnetic nanoparticles have also found application as signal labels in biosensing systems, such as molecular detection and related strategies that rely on ligand-receptor binding. In particular, iron oxide magnetic nanoparticles (NPs), such as magnetite (Fe 3 O 4 ) and maghemite (γ-Fe 2 O 3 ), are particularly appealing due to their magnetic properties, tunable size, biocompatibility, and greater ease of synthesis than other magnetic materials [ 20 , 21 , 22 ]. Indeed, recent studies have shown how to use magnetic nanoparticles to improve the efficiency of the functionalization process [ 23 ], to realize multiplexing immunoassays [ 24 ] and for magnetic detection [ 14 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%